New Lipsothrix (Diptera: Limoniidae) from Korea - Podenas, Sigitas; Petersen, Matthew; Kim, A-Young; Park, Sun-Jae; Byun, Hye-Woo; Seo, Hong-Yul (Zootaxa, 2019)
Lipsothrix odaesana Podenas & Petersen, sp. nov. from South Korea is described and illustrated. It is the only species of Lipsothrix Loew, 1873 recorded so far from the Korean Peninsula. Elevation range, period of activity, habitat information and a distribution map are presented.